Law and truth - Patterson, Dennis Michael (Dennis Michael), 1955- (New York : Oxford University Press, 1996)
Taking up a single question--"What does it mean to say a proposition of law is true?"--This book advances a new account of truth in law. Drawing upon the later philosophy of Wittgenstein, as well as more recent postmodern theory of the relationship between language, meaning, and the world, Patterson examines leading contemporary jurisprudential approaches to this question and finds them flawed in similar and previously unnoticed ways. He offers an alternative account of legal justification, one in which linguistic practice--the use of forms of legal argument--holds the key to legal meaning
Introduction : realism, anti-realism, and legal theory -- Legal formalism : on the immanent rationality of law -- Moral realism and truth in law -- Legal positivism -- Law as interpretation : the jurisprudence of Ronald Dworkin -- Law as an interpretive community : the case of Stanley Fish -- Truth in law : a modal account -- Postmodern jurisprudence
Includes bibliographical references and index (pages 183-189).
Keywords: Truth; Jurisprudence; Law -- Philosophy